Exploring and Expanding Through 'Real-World' Tasks: The Digital Practices of Generation Z Post-Secondary FSL Learners - Douglas, Shayna (Université d'Ottawa / University of Ottawa, 2023)
This exploratory case study examined the digital practices and literacies of Generation Z language learners and explored how these practices could be better addressed in the language classroom through "Real-World" tasks. The study was conducted within the theoretical framework of the Sociocultural Approach to Language Learning and the pedagogical framework of the Real-World Task-Based Language Teaching approach, with an emphasis on the eLANG citizen project. The data was analyzed through qualitative thematic analysis of both a corpus of learner final reports and two questionnaires, resulting in a detailed portrait of the learners' digital practices. The findings indicate that implementing real-world, task-based language learning projects that utilize Generation Z's pre-existing digital competencies can lead to improved language and digital literacy skills. Students reported enhancements in their oral expression, use of slang, and interaction with native speakers, as well as improvements in their understanding of hashtags, video planning and editing, and trend tracking. The students had multiple real-world, authentic interactions through the digital citizenship project, which enabled them to become enhanced digital citizens in FLS by formulating their identities, observing established communities and language users, participating in these communities directly, and learning in informal, gameful ways. It is proposed that utilizing the digital practices of Generation Z learners for language learning not only enhances the authenticity and relevance of the activities but also helps to achieve pedagogical objectives. This prepares learners for their future in a technology-saturated world and becoming effective members of society and is the next relevant step in sociocultural language pedagogy.
Keywords: social media; digital citizenship; digital wilds; task-based learning; Generation Z; real-world tasks; digital literacy